Control Lyapunov function for feedback stabilization of affine in the control stochastic time-varying systems. - Abedi, Fakhreddin; Abu Hassan, Malik; Md. Arifin, Norihan (Hikari Ltd, 2011)
The aim of this paper is to study the problem of nonuniform in time global asymptotic stability in probability of affine in the control stochastic time-varying systems. We extend Artstein-Sontag theorem to the concept of control Lyapunov function to derive the necessary and sufficient conditions for feedback stabilization for affine in the control stochastic time-varying systems.